INFLUENCE OF LEADERSHIP STYLES TOWARDS ORGANIZATIONAL COMMITMENT - Suman, Mahindreen; Qistina Donna, Lee Abdullah; Khashini Devi, R. Varatharajoo (UNIMAS Publisher, 2019)
This research endeavours to explore the impact of leadership styles towards organizational commitment in influencing employees and employer’s outcomes in the context of organizational commitment. Based on this theory, two leadership styles practices, namely, Transformational Leadership and Transactional Leadership, have been used to examine employees’ and employer’s reactions towards commitment in the organization chosen which is Amogha Maju Sdn Bhd, Kuching, Sarawak. Data were acquired from employees in administrative level through interview questions. Thus, researcher acknowledge that the employees were influenced by Transactional and Transformational Leadership Styles.